Factors Related of Musculoskeletal Disorders (MSDS) Complain in Online Study at Public Health University X - Ardi, Subhan Zul; Hidayah, Qonitatul (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Ergonomics problems are related to the presence of discomfort when doing work, so that the impact on complaints of a disease is no exception felt by students during lectures using the online method. In this study, there were problems, including 7 respondents who stated that their back and neck felt pain, 8 people felt watery, and pungent in the eyes. Different sleep times of 7 respondents. Different lecture times between classes of 7 respondents. The study goal was to analyze the element related to complaints of musculoskeletal disorders in online study for students’ class 2020 at the Faculty of Public Health.: Methods of this study was a quantitative descriptive, with a population of 238 students from the class of 2020, and a research sample of 71 students. The sampling technique used incidental. The instruments tool used noordic body map, and REBA sheet. The data analysis used Chi-square test. There was relationship between gender and the duration study and there was no correlation between sleep time and musculoskeletal complaints in students’ class 2020 at the Faculty of Public Health University X with p = 0.41, 0.39 and 0.886. There is a relationship between gender and duration study and there is no correlation between sleep time and musculoskeletal complaints in online study in students’ class 2020 of the Faculty of Public Health, University X.